2018
DOI: 10.1371/journal.pntd.0005967
|View full text |Cite
|
Sign up to set email alerts
|

Improved tools and strategies for the prevention and control of arboviral diseases: A research-to-policy forum

Abstract: BackgroundResearch has been conducted on interventions to control dengue transmission and respond to outbreaks. A summary of the available evidence will help inform disease control policy decisions and research directions, both for dengue and, more broadly, for all Aedes-borne arboviral diseases.MethodA research-to-policy forum was convened by TDR, the Special Programme for Research and Training in Tropical Diseases, with researchers and representatives from ministries of health, in order to review research fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 35 publications
0
41
0
3
Order By: Relevance
“…aegypti serving as the principal vector in many South American countries, including Ecuador [2]. Due to the lack of commercially available vaccines for most human arboviral diseases, prevention efforts focus on vector surveillance and control methods [3].…”
mentioning
confidence: 99%
“…aegypti serving as the principal vector in many South American countries, including Ecuador [2]. Due to the lack of commercially available vaccines for most human arboviral diseases, prevention efforts focus on vector surveillance and control methods [3].…”
mentioning
confidence: 99%
“…Olliaro P, et al (2018) beside writing in a same manner on critical-characteristic that an alert system should have to document trend reliably and trigger timely response (i.e., early enough to prevent the epidemic spread of the virus) to dengue outbreaks addressing a range of variable(s) that either indicate risk of forthcoming dengue transmission or predict dengue outbreaks that could be successfully applied to Early Warning and Response System (EWARS), had also written that summary of published literature show that controlling Aedes vectors require complex-intervention and point to the need in standardized energetic-effort with disease-reduction as the measured primary outcome. Sampling vector populations, both here in a surveillance-aim and evaluation of controlactivity, many a such researcher claim is usually seen carried out in an unsystematic way, limiting the potential(s) of entomological-surveillance toward outbreak prediction [24].…”
Section: Use Of Novel Ovi-trap and Various Innovativemethodsmentioning
confidence: 99%
“…A literature review conducted by Olliaro et al (2018) found that controlling the Aedes vector requires complex intervention. A community-based approach and the public sector will empower risk populations, reduce intervention costs, build sustainability, and increase the impact of vector control interventions.…”
Section: Introductionmentioning
confidence: 99%